2015
DOI: 10.1038/nrurol.2015.193
|View full text |Cite
|
Sign up to set email alerts
|

Current and potential urological applications of botulinum toxin A

Abstract: Botulinum toxin subtype A (BoNT-A) is a potent neurotoxin that can selectively modulate neurotransmitter release from nerve endings, resulting in muscular paralysis. BoNT-A might also act on sensory nerves, and have an anti-inflammatory effect. In the first urological use of BoNT-A, injection into the urethral sphincters of patients with detrusor-sphincter dyssynergia resulted in a reduction of urethral resistance and improved voiding efficiency. Subsequently, intravesical BoNT-A injections have received regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 161 publications
(214 reference statements)
0
38
0
1
Order By: Relevance
“…For the same reason sub urothelial injection may be interesting. Finally, new technics allowing a homogenous diffusion of Botox®, without any pain, such as electromotive administration, deserve to be developed, even‐though long‐term evaluation of those techniques are still missing . .…”
Section: Discussionmentioning
confidence: 99%
“…For the same reason sub urothelial injection may be interesting. Finally, new technics allowing a homogenous diffusion of Botox®, without any pain, such as electromotive administration, deserve to be developed, even‐though long‐term evaluation of those techniques are still missing . .…”
Section: Discussionmentioning
confidence: 99%
“…The brief description of probable sensory disturbances occurrence are illustrated in Figure 1. The sensory disturbances of an unstable bladder may elicit from activation of silence C-fibers due to noxious stimuli (1), stretching stretch-mediated receptors, and myofibroblasts (2), chemicals inducing urothelial signaling (3), and signals generated in a modulated motor-sensory system (4).…”
Section: Sensory Bladder Disordersmentioning
confidence: 99%
“…Recent studies have additionally shown an anti-inflammatory effect and reduction of substance P in the urine following intradetrusor BTX-A injection. 19,20 Sacral nerve stimulation (SNS) is not widely available. It involves placing a lead into sacral foramen S3, connected to an implantable neurostimulator under the skin just above the sacrum.…”
Section: Surgical Optionsmentioning
confidence: 99%